The Possibilities of Open and No Borders - Bauder, Harald (Social justice, 2012)
An overarching constraint for free human mobility is that international political borders are only selectively permeable. Drawing on Ernst Bloch's work on the possible, the author examines open-borders and no-border arguments and explores the conditions of their possibilities. Although open-borders and no-border narratives serve as a powerful negation of contemporary conditions of closed and/or controlled borders, the possibility of free human mobility would either require the reconfiguration of existing citizenship principles and practices or more substantive structural transformations. Domicile-based citizenship could facilitate open borders under existing political configurations, whereas no border would require a fundamental rearrangement of the geographies of mobility and belonging.